2010
DOI: 10.4103/0972-124x.65427
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic activity of peripheral blood and crevicular phagocytes in health and periodontal disease

Abstract: Background:Neutrophils constitute the main phagocytic cell system in mammalian host defense against an infecting agent. Abnormalities in leukocyte number and function are associated with increased susceptibility to periodontal diseases. The purpose of this study is to evaluate the in vitro phagocytic properties of crevicular and peripheral blood neutrophils in healthy and periodontitis subjects.Patients and Methods:A total of 30 subjects, that is, 10 patients in each of the following three groups: healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
12
0
3
Order By: Relevance
“…According to our findings, during periodontitis before the According to the literature, during periodontitis peripheral neutrophils phagocytic activity is changing [Asif K, et al 2010]. Phagocytic index is lowered and accordingly lowers the phagocytic neutrophils percentage [Carneiro VMA et al, 2012].…”
Section: Discussionmentioning
confidence: 63%
“…According to our findings, during periodontitis before the According to the literature, during periodontitis peripheral neutrophils phagocytic activity is changing [Asif K, et al 2010]. Phagocytic index is lowered and accordingly lowers the phagocytic neutrophils percentage [Carneiro VMA et al, 2012].…”
Section: Discussionmentioning
confidence: 63%
“…This is in accordance with three previous studies. 23,33,34 Our data further show that when GCF was analyzed for the presence and levels of βG activity, the presence of detectable levels of βG was shown in all the subjects. However, the diseased patients at the baseline presented higher enzyme activity than the periodontally treated patients.…”
Section: Discussionmentioning
confidence: 79%
“…10,35 As indicated in previous studies conducted on various GCF components, including enzymes, the highest GCF βG activity was found in patients with disease when no treatment was initiated. 10,[31][32][33][34][35] This increase in βG can be attributed to the hyperactive state and pronounced response of PMN as a consequence of the severity of microbial virulence factors and also to the lytic effect of more pathogenic subgingival bacteria on host cells leading to an intense host enzyme release.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis contributes to host defence by recognizing and eliminating invading pathogens (Soehnlein & Lindbom 2010). Recently, it was shown that in vitro phagocytic activity of crevicular and peripheral blood neutrophils, obtained from localized aggressive periodontitis patients, is reduced (Asif & Kothiwale 2010). To determine the ability of gingipains to disrupt phagocytosis, we used the in vivo phagocytosis assay.…”
Section: Discussionmentioning
confidence: 99%